Legitimation of the Authority of Legal Actions of the Corruption Eradication Commission (KPK) Against Criminal Acts of Corruption - Nana Lukmana; Subianta Mandala (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The crime of corruption has become a very complicated and complicated problem related to many problems that are interconnected with each other, including the relationship with the impact on the administration of the state. For this reason, the activity of eradicating corruption, as a form of reform in eradicating corruption in Indonesia based on Law Number 30 of 2002 concerning the Corruption Eradication Commission (KPK), is given to the Corruption Eradication Commission (KPK). The problems are: What is the authority of the Corruption Eradication Commission (KPK) in taking legal action against perpetrators of criminal acts of corruption? The research method in this research framework uses a normative or doctrinal legal research approach or legal research. It means that the object of study in this research focuses on discussing the legitimacy of the legal action authority of the Corruption Eradication Commission (KPK) against perpetrators of corruption. This research is descriptive analytical and in the form of a descriptive study. The data sources used are secondary data sources and primary data sources. Data collection is done through literature study. Data analysis in this study was carried out qualitatively. The results of the research and discussion of this problem in essence, that philosophically the legal remedy strategy as a form of reform in eradicating corruption in Indonesia, that the Corruption Eradication Commission (KPK), is an alternative to a law enforcement institution considering that existing institutions are not considered effective enough in take legal action and efforts in eradicating corruption. The authority of the Corruption Eradication Commission (KPK) in taking legal action against perpetrators of criminal acts of corruption, is given several privileges, among others; take over a case of criminal acts of corruption committed by police investigators and prosecutors investigators because they are considered sluggish, supervise the police and prosecutors' institutions that carry out legal actions and remedies related to corruption crimes, and the Corruption Eradication Commission may not issue a Letter of Termination of Case Investigation (SP3) related corruption crimes are handled